Towards Systematization - Reichertz, P. L. (Methods of Information in Medicine, 1977)
Data processing has become an important tool in theoretical and clinical medicine. The main categories of applications are : information analysis, (bio)signal processing and the field of information logistics (information systems).The problems encountered lie in the discrepancy of the basic methods of a formal approach to an empirical science, the complexity of the target system and the system ecology, i.e. the involvement of the user and the system environment during system construction and utilization.Possible solutions to these problems are the application of system techniques, inductive planning, development of medical methodology, development of methods and techniques for user involvement and assessment of motivation and education and educational planning.The necessary general strategy in the development in medical informatics is seen in the continuing systematization of the theoretical and practical approach. It is estimated that this will eventually contribute to the systematization of medical science and practice.
Keywords: Medical Informatics; Problems of Application; Systematization; User Research; Medical Methodology